2020
DOI: 10.1136/ijgc-2019-000930
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node mapping in endometrial cancer: performance of hysteroscopic injection of tracers

Abstract: ObjectiveTo report on the performance of hysteroscopic injection of tracers (indocyanine green (ICG) and technetium-99m (Tc-99m)) for sentinel lymph node (SLN) mapping in endometrial cancer.MethodsSingle-center retrospective evaluation of consecutive patients who underwent SLN mapping following hysteroscopic peritumoral injection of tracer. Detection rate (overall/bilateral/aortic) diagnostic accuracy, and oncologic outcomes were evaluated.ResultsA total of 221 procedures met the inclusion criteria. Mean patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…The detection rate of this technique ranges from 50% to 95% [ 11 35 ]. A recent study has reported a paraaortic SLN detection rate by hysteroscopic injection with radiotracer or ICG similar to the present series [ 30 ]. However, a randomized trial comparing cervical and hysteroscopic injections showed better identification of pelvic SLNs after cervical injection with a non-significant higher detection rate of paraaortic SLNs after hysteroscopic injection [ 36 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The detection rate of this technique ranges from 50% to 95% [ 11 35 ]. A recent study has reported a paraaortic SLN detection rate by hysteroscopic injection with radiotracer or ICG similar to the present series [ 30 ]. However, a randomized trial comparing cervical and hysteroscopic injections showed better identification of pelvic SLNs after cervical injection with a non-significant higher detection rate of paraaortic SLNs after hysteroscopic injection [ 36 ].…”
Section: Discussionsupporting
confidence: 87%
“…This is concordant with the extremely low detection of isolated paraaortic SLNs of less than 1% [ 29 ], which is inferior to the exclusive paraaortic drainage with the TUMIR approach (7.4%). This low percentage is not surprising, since it has been already pointed out that cervical injection does not adequately represent endometrial drainage, because it misses the lymphatic drainage to the paraaortic area [ 30 ]. The uterine corpus has 2 simultaneous lymphatic pathways: the first drainage is through the lymphatic channels together with the uterine vessels to the pelvic LNs -located in the lateral part of the parametrium and/or under the external iliac vein-, and the second drainage goes directly to the paraaortic area through the lymphatic vessels of the gonadal vasculature and the infundibulopelvic ligament [ 31 ], explaining the possibility of having SLNs in both areas independently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations